Analysis of multiple failure behaviors of steering knuckle ball hinge of multi-axle heavy vehicle. (October 2021) - Wang, Zhenyu; Wei, Shuo; Bao, Ke; Liu, Yue; Peng, Senye; Zhang, Qing
The ball hinge is a key component of the vehicle chassis that connects the steering knuckle and the control arm. The study analyzed the multiple failure behaviors of the chassis ball hinge. Firstly, according to the macroscopic failure characteristics of the ball hinge, the fault tree analysis method was adopted to identify the possible cause of the failure. Then, the axial load and radial load on the ball joint were obtained by simulating the force of the vehicle under the typical extreme conditions. The stress distribution of the ball pin was obtained by finite element analysis of the ball joint. The calculation results are consistent with the fatigue crack position of the ball hinge. Finally, the macro morphology and microstructure of the ball joint seat, ball bowl, dust cover and other parts matched with the ball hinge were analyzed to further verify the failure mode of the ball hinge. The results showed that the dust cover of the ball hinge was firstly aged and cracked, and the external dust and particles enter into the friction contact area of the ball hinge, which caused the ball pin and ball bowl to be stuck. During the operating of the vehicle, the ball pin undergoes unidirectional bending fatigue fracture in the stress concentration area at the root of the conical surface.